Value chains transform Kenyan farmer groups into entrepreneurial entities - Muchai, Daphne (Technical Centre for Agricultural and Rural Cooperation, 2018)
The "Enhancement of Farmer Entrepreneurship for Development" programme is facilitating smallholder farmer capacity building and stakeholder engagement in Kenyan counties, to enable farmer groups to become more business oriented. The programme has also analysed the priority agricultural product value chains to identify opportunities within the markets.